2018
DOI: 10.5603/cj.2018.0154
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent right bundle branch block in a child with familial mediterranean fever

Abstract: Complete right bundle branch block (RBBB) results when normal electrical activity in the His-Purkinje system is interrupted. The most common cause of RBBB is surgical closure of ventricular septal defects, especially in tetralogy of Fallot [1]. Rare cases of isolated, familial RBBB have also been reported [2].Although a large number of intermittent left bundle branch block (LBBB) cases commonly associated with coronary heart disease have been reported in adults, a very small number of intermittent RBBB cases h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Incidentally, it was discovered soon after the initial workup that our patient also had added heart sounds, who was later diagnosed to have pericardial effusion. Abukhalaf and Ceylan et al [13,14] also reported cardiac complications among their patients, namely cardiac amyloidosis and right bundle branch block, respectively. Despite the differences in age groups, clinical presentations, family history, or laboratory results, colchicine remains the first-line treatment modality for a majority of the tabulated patients, with documented recovery.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Incidentally, it was discovered soon after the initial workup that our patient also had added heart sounds, who was later diagnosed to have pericardial effusion. Abukhalaf and Ceylan et al [13,14] also reported cardiac complications among their patients, namely cardiac amyloidosis and right bundle branch block, respectively. Despite the differences in age groups, clinical presentations, family history, or laboratory results, colchicine remains the first-line treatment modality for a majority of the tabulated patients, with documented recovery.…”
Section: Discussionmentioning
confidence: 92%
“…Incidentally, it was discovered soon after the initial workup that our patient also had added heart sounds, who was later diagnosed to have pericardial effusion. Abukhalaf and Ceylan et al [ 13 , 14 ] also reported cardiac complications among their patients, namely cardiac amyloidosis and right bundle branch block, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation